Designing virtual meetings: Reviewing virtual meeting design through the lens of media naturalness - Darien Tartler; Lisa Handke; Simone Kauffeld (Electronic Markets, 2025)
Abstract Virtual meetings are here to stay. However, research on the design of these meetings is scarce. To summarize the current state of research on virtual meeting design, we identified 31 studies examining how temporal, physical, procedural, and attendee characteristics affect various within- and post-meeting success factors through media naturalness. Twenty-one of these studies discussed physical design enabling new technological interaction possibilities. Six studies dealt with procedural design and showed opportunities for shaping virtual meetings through structural measures. Four studies related to temporal and three studies to attendee characteristics, which showed further options to influence virtual meetings through time and in-person characteristics. Overall, the effect of virtual meeting design can be complex and opens up a wide field for research and practical applications. Our results are discussed against the background of media naturalness through which we identify the most pressing research directions, questions, and designs to advance knowledge on virtual meetings.
Additional information: M14;M54;O33
Keywords: 330; Virtual meetings; Meeting design; Meeting success factors; Virtual collaboration; Media naturalness